Multisensory cortical processing and dysfunction across the neuropsychiatric spectrum. (February 2019) - Hornix, Betty E.; Havekes, Robbert; Kas, Martien J.H.
Highlights: Morphogens and internal spontaneous activity guide neuronal projections in sensory circuits. Sensory circuit development continues until early adulthood. Sensory brain maps are aligned to integrate stimuli from different senses. Social cue processing requires a high level of multisensory integration. Abstract: Sensory processing is affected in multiple neuropsychiatric disorders like schizophrenia and autism spectrum disorders. Genetic and environmental factors guide the formation and fine-tuning of brain circuitry necessary to receive, organize, and respond to sensory input in order to behave in a meaningful and consistent manner. During certain developmental stages the brain is sensitive to intrinsic and external factors. For example, disturbed expression levels of certain risk genes during critical neurodevelopmental periods may lead to exaggerated brain plasticity processes within the sensory circuits, and sensory stimulation immediately after birth contributes to fine-tuning of these circuits. Here, the neurodevelopmental trajectory of sensory circuit development will be described and related to some example risk gene mutations that are found in neuropsychiatric disorders. Subsequently, the flow of sensory information through these circuits and the relationship to synaptic plasticity will be described. Research focusing on the combined analyses of neural circuit development and functioning are necessary to expand our understanding of sensory processing and behavioral deficits that are relevant across the neuropsychiatric spectrum.